Serum chemokines combined with multi-modal imaging to evaluate atherosclerotic plaque stability in patients undergoing carotid endarterectomy - Yuan, Xiaofan; Guo, Lei; Chen, Hong; Gao, Yang; Guo, Fuqiang; Huang, Jie; Jiang, Chuan; Wang, Zhenyu (Frontiers in Neurology, 2025)
BackgroundAlthough imaging tools are crucial in identifying features of atherosclerotic plaque, there remains a lack of consensus on the use of serological markers for assessing high-risk plaques.MethodsPatients diagnosed with CAS who met the criteria for CEA were categorized as the operation group, while those without CAS were designated as the control group. Multi-modal imaging was conducted pre- and post-CEA to evaluate plaque features, such as the volume of calcification and LRNC, intra-plaque hemorrhage, and the degree of carotid stenosis. Serum chemokine levels were measured in both groups before CEA and on the 7th day post-surgery. Morphological features of carotid artery specimens were assessed using H&E and IHC (CD68 and α-SMA) staining to evaluate plaque stability.ResultsNo significant differences in the degree of CAS between the operation and control groups. Among the operation group, 26 out of 52 patients were identified as vulnerable plaques. The volume of LRNC was significantly higher in vulnerable plaque, whereas the volume of calcification was significantly lower in vulnerable plaque compared to stable plaque confirmed by multi-modal imaging. Vulnerable plaque exhibited a thin fibrous cap covered an LRNC, intra-plaque hemorrhage, and macrophage infiltration. Stable plaque were characterized by small lipid cores covered by a thick fibrous cap, with minimal macrophage infiltration. Chemokine levels were significantly elevated in CAS patients compared to controls, and decreased significantly on the 7th day post-CEA. In patients with vulnerable plaque, lower levels of CX3CL1, CXCL12, CCL19, and CCL21, but higher levels of CCL2 and CCL5, were observed compared to patients with stable plaque. Correlation analysis further indicated that CX3CL1 and CXCL12 levels were positively associated with calcification volume. While CCL2 and CCL5 levels were positively associated, and CCL19 and CCL21 negatively associated, with LRNC volume. Multivariate analysis suggested that CXCL12 was an independent protective factor and LRNC volume as an independent risk factor for plaque vulnerability. The combination with multi-modal imaging and serological markers enhanced both the sensitivity (87.31%) and specificity (92.31%) in predicting plaque stability, with an AUC of 0.9001.ConclusionCombining multi-modal imaging with serological markers provides a more comprehensive evaluation of atherosclerotic plaque features.